Methods for Accelerating the Fluorescent-Antibody Test for Rabies Diagnosis - Larghi, Oscar P. (1971)
The time required to perform the fluorescent-antibody test for rabies was reduced by eliminating acetone fixation of the brain impressions and by incubating the conjugate-impression reaction at room temperature for only 10 min. Elimination of the preliminary acetone fixation had no effect on the diagnosis of impression smears from 246 mammalian brains by immunofluorescence. Staining at 37 C for 30 min and staining at room temperature for 10 min were found to be equally effective in the examination of impression smears from 161 brain samples. The procedure, as modified, shortens the time required for the diagnosis of rabies by immunofluorescence from about 5.5 hr to approximately 45 min.